Inventory of Bandar Aceh Darussalam's Keuh Coins as a Collection of the North Sumatra Quranic History Museum - Khairul Tamimi; Muaz Tanjung; Kasron Nasution (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
The Keuh coins of Bandar Aceh Darussalam, made from tin, served as currency during the Aceh Darussalam Sultanate. Known as Caxa by the Portuguese and Kasha by the Dutch, these coins varied in value depending on cultural contexts. This study aims to inventory, identify, and describe the Keuh coins of Bandar Aceh Darussalam within the collection of the Museum of Quranic History in North Sumatra. Employing a qualitative method with a descriptive-analytical approach, data collection involved direct observation of the coins. The identification and description processes included measurements of weight, diameter, and thickness, alongside an analysis of inscriptions found on the coins. Findings reveal that the Museum of Quranic History in North Sumatra houses a collection of 39 Keuh coins from Bandar Aceh Darussalam, showcasing variations in size and inscriptions. This inventory is essential for the preservation and promotion of cultural heritage. The study also highlights the importance of engaging multiple stakeholders to increase public awareness of the museum's collection. The detailed identification and description of the Keuh coins aim to foster a broader understanding and appreciation of these historical artifacts among diverse audiences.